2018
DOI: 10.1017/jog.2018.56
|View full text |Cite
|
Sign up to set email alerts
|

Increasing contribution of grain boundary compliance to polycrystalline ice elasticity as temperature increases

Abstract: ABSTRACT. Measured elastic stiffnesses of ice polycrystals decrease with increasing temperature due to a decrease in grain boundary stiffness with increasing temperature. In this paper, we represent grain boundaries as imperfectly bonded interfaces, across which traction is continuous, but displacement may be discontinuous. We express the additional compliance due to grain boundaries in terms of a second-rank and a fourth-rank tensor, which quantify the effect on elastic wave velocities of the orientation dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The ability of a CPO model to explain measured seismic anisotropy is assessed by introduction of a misfit between synthetic forward modelled seismic properties and observations. We found that CPO predicted seismic velocities are consistently faster than observed velocities, an effect which can be attributed to the absence of grain boundary effects (Sayers, 2018) or air bubbles…”
Section: Model Misfit Calculationmentioning
confidence: 63%
“…The ability of a CPO model to explain measured seismic anisotropy is assessed by introduction of a misfit between synthetic forward modelled seismic properties and observations. We found that CPO predicted seismic velocities are consistently faster than observed velocities, an effect which can be attributed to the absence of grain boundary effects (Sayers, 2018) or air bubbles…”
Section: Model Misfit Calculationmentioning
confidence: 63%
“…The ability of a CPO model to explain measured seismic anisotropy is assessed by introduction of a misfit between synthetic forward-modelled seismic properties and observations. We found that CPO-predicted seismic velocities are consistently faster than observed velocities, an effect which can be attributed to the absence of grain boundary effects (Sayers, 2018) or air bubbles (Hellmann et al, 2021) in synthetic CPOs. The elasticity tensor by Gammon et al (1983) was derived using oscillations in gigahertz (GHz) frequencies; therefore dispersion is another potential factor to introduce differences between modelled and observed seismic or ultrasonic velocities with hertz (Hz) to kilohertz (kHz) frequencies.…”
Section: Model Misfit Calculationmentioning
confidence: 64%
“…At the site the glacier is ∼ 1000 m thick and 8 km wide (Frezzotti et al, 2000). Ice flow velocities are measured to increase from ∼ 45 m yr −1 close to the glacier margin to ∼ 130 m yr −1 towards the centre (Mouginot et al, 2019;Thomas et al, 2021), resulting in strong shear, with shear strain rates at the site calculated to be 6 × 10 −10 s −1 (Still et al, 2022;Thomas et al, 2021). Core samples were analysed for CPO using electron backscatter diffraction (EBSD) measurements (Thomas et al, 2021), and a strong horizontal clustering of c axes was observed throughout the entire length of the core.…”
Section: Introductionmentioning
confidence: 91%
“…It then follows (Sayers and Han, 2002; Sayers, 2018) that the bulk and shear moduli of the medium in the presence of imperfect bonds between the ice particles are:where K 0 and μ 0 are the bulk and shear moduli that would result if the bonds between ice particles were perfect. It follows from Eqns (15) and (16) that 5 β /(3α) = ( B N / B S ) − 1, assuming an isotropic distribution of normal vectors n i .…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that snow and firn are isotropic, the non-vanishing components of α ij and β ijkl are: It then follows (Sayers and Han, 2002;Sayers, 2018) that the bulk and shear moduli of the medium in the presence of imperfect bonds between the ice particles are:…”
Section: Journal Of Glaciologymentioning
confidence: 99%